Isolation of the human chromosomal band Xq28 within somatic cell hybrids by fragile X site breakage. - Warren, S; Knight, S; Peters, J; Stayton, C; Consalez, G; Zhang, F (1990)
The chromosomal fragile-site mapping to Xq27.3 is associated with a frequent form of mental retardation and is prone to breakage after induced deoxyribonucleotide pool perturbation. The human hypoxanthine phosphoribosyltransferase (HPRT) and glucose-6-phosphate dehydrogenase (G6PD) genes flank the fragile X chromosome site and can be used to monitor integrity of the site in human-hamster somatic cell hybrids deficient in the rodent forms of these activities. After induction of the fragile X site, negative selection for HPRT and positive enrichment for G6PD resulted in 31 independent colonies of HPRT-,G6PD+ phenotype. Southern blot analysis demonstrated the loss of all tested markers proximal to the fragile X site with retention of all tested human Xq28 loci in a majority of the hybrids. In situ hybridization with a human-specific probe demonstrated the translocation of a small amount of human DNA to rodent chromosomes in these hybrids, suggesting chromosome breakage at the fragile X site and the subsequent translocation of Xq28. Southern blot hybridization of hybrid-cell DNA, resolved by pulsed-field gel electrophoresis, for human-specific repetitive sequences revealed abundant CpG-islands within Xq28, consistent with its known gene density. The electrophoretic banding patterns of human DNA among the hybrids were remarkably consistent, suggesting that fragile X site breakage is limited to a relatively small region in Xq27-28. These somatic cell hybrids, containing Xq27.3-qter as the sole human DNA, will aid the search for DNA associated with the fragile X site and will augment the high resolution genomic analysis of Xq28, including the identification of candidate genes for genetic-disease loci mapping to this region.